Compact Bandpass Filters Using Dual-Mode Microstrip Closed-Loop Ring Resonators for Wireless Communication Systems - Esfeh, Babak Kazemi (2009)
Microwave filters have important role in many wireless and communication systems such as satellite and cellular mobile organizations. In such kind of systems, factors such as compact size, low cost, light weight, high performance, and low loss in designing of microwave filters are of primary importance. In comparison with waveguide filters, microstrip filters are smaller and in such applications mentioned before there are needs to have smaller microstrip filters. In this thesis, filters using dual-mode ring resonators is proposed, because they can be designed easier than the other kind of microwave filters and are more compact. In this thesis, a new compact form of dual-mode microstrip octagonal loop resonator filter is proposed in two forms; conventional and compact. These structures are designed to operate at WiMax frequency of 2.3 GHz with a 5% fractional bandwidth. The new dual-mode resonator will be produced by adding a rectangular patch inside the loop resonator. The experimental results and simulated values are presented and show good agreement. The filter is fabricated on CER-10 substrate having a relative dielectric constant of 10 and 0.64 mm thickness. The primary dimension of the filter is 15.8 mm´15.8 mm and the measured minimum insertion loss is 1.68 dB and return loss is better than -20 dB. After minimization and compressing the filter structure, the final dimension is reduced to 9.1 mm´9.1 mm. The minimum insertion loss in this structure is 1.52 dB and the return loss is better than -20 dB. In the final design in addition to size reduction (about 42%), feed lines structure is changed from orthogonal to straight line form, which are more desirable in microwave networks. This new design is reduced in size by approximately 25% compared to the conventional square loop dual-mode filter. By using meander square loop structure more reduction in size (about 27%) can be achieved but this filter configuration has a weak frequency response including high passband insertion loss (more than 2.6 dB) and return loss less than -12dB at the same center frequency. Therefore its performance is less than the dual-mode filter proposed in this thesis. Apart from WiMax, this model of filters is also useful for WLAN and mobile communication applications, because it is compact in size, low loss and has good performance due to its elliptic response with sharp rejection and adequate fractional bandwidth.